Modal Sosial dan Kemiskinan Rumah Tangga di Indonesia - Agustinur Saputri (Jurnal Kawistara, 2021)
Poverty has been continuously seen as a critical global challenge issue faced by many countries across the continents. As one of the main goals of Sustainable Development Goals (SDGs), strategies to overcome poverty have become interesting topics in discussions on both a global and national scale. In Indonesia, the issue of poverty alleviation still occupies the national development priority. Interestingly, the government agendas for combating poverty now include a plan to incorporate the role of social capital. This raises a question of how social capital might help in the agenda of alleviating poverty that has been dominantly seen as a structural issue? This study aimed to examine the condition of social capital in Indonesia according to the dimensions and areas of residence, and the effect of social capital on household poverty in Indonesia. Using the National Socioeconomic Survey (Susenas) data of September 2018, this study was analyzed descriptively and inferentially. The study showed that the households’ social capital in rural areas was higher than households in urban areas. The dimension of collective action was the strongest dimension in Indonesia’s social life, both in rural and urban, which was then followed by the dimensions of trust and tolerance as well as groups and networks. Binary logistic regression analysis found that social capital had a significant negative effect on household poverty. Control variables such as areas of residence, household head’s gender, household head's marital status, number of household members, household head’s age, household head's education level, and household head’s main occupation also affected household poverty.